Zn–porphyrin metal–organic framework–based photoelectrochemical enzymatic biosensor for hypoxanthine - Wang, Yujun; Tu, Rongxiu; Hou, Chuantao; Wang, Zonghua (Journal of solid state electrochemistry, 2022)
The exploitation of metal–organic frameworks as photoactive materials for photoelectrochemical (PEC) sensing is of great importance because of their unique structures and specific PEC properties. Herein, a porphyrin-MOF was coupled with oxidase to develop a PEC enzymatic sensor. Specifically, a nanoscale Al-TCPP(Zn) (Zn-TCPP = Zn-tetrakis(4-carboxyphenyl)porphyrin) was synthesized by adjusting the reaction solvents, and its photophysical properties were investigated by spectral and electrochemical techniques. The Al-TCPP(Zn) showed stable cathodic photocurrents, which are dependent on the dissolved oxygen in phosphate buffer. After the coupling with xanthine oxidase, the developed PEC enzymatic sensor showed enhanced responses towards the increased concentration of hypoxanthine with a low limit of detection, excellent selectivity, and reusability. This study combines the advantages of MOF-based PEC sensing and enzyme sensing, providing great potential to develop high-performance PEC bioanalysis. Graphical abstract